Guns, Lawyers, and Markets: On Economic and Political Consequences of Costly Conflict - Stergios Skaperdas; Samarth Vaidya (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We synthesize research on conflict as a fundamental economic phenomenon, arguing that the implications of the "dark side of self-interest" have received insufficient attention in economics. We define conflict as interactions where parties choose costly inputs that are adversarially combined against one another — distinct from the collaborative input combinations typical in economic models. We make four key contributions: First, we demonstrate that conflict induces economically significant costs comparable to or exceeding traditional deadweight losses. Second, we explain how these costs vary across contexts based on property rights protection, state capacity, and cultural norms. Third, we show how incorporating conflict into economic models leads to substantially different predictions than traditional models — including inverse relationships between compensation and productivity; distortions in comparative advantage; prices determined by power rather than solely by preferences endowments, and technology. Fourth, attributes of modern states such as centralization in the presence of law, checks and balances, other forms of distributed power, and the bureaucratic form of organization can partly be thought of as restraining conflict and appropriation, with implications for governance and economic development. Overall, in the presence of conflict and appropriation, power considerations cannot be separated from economics and first-best models are not empirically plausible.
Keywords: A12; D30; D51; D61; D72; D74; F51; K00; P00; 330; conflict; appropriation; security; property rights; power; the modern state; rent-seeking; contests